Technological aspects of production of frozen dessert with protein-herbal component - Grek, Olena; Osmak (Fedchenko), Tetiana; Chubenko, Larysa; Mykhalevych, Artur (My University, 2018)
The emergency of the development of new frozen desserts with protein-milk concentrates, obtained by different coagulation methods, is substantiated. The advantages of using the thermo & heat coagulation of milk proteins are taken into consideration. Having in view the complex influence on the proteins of high temperature milk and the Rumex acid reagent, the parameters of the process are specified. As raw material for coagulation, skimmed milk with a mass fraction of dry matter of 11.2 ± 0.7%, protein, 3.7 ± 0.2%, titrated acidity, 17 ± 1.0°T, density, 1032 kg/m3 was selected. The amount of coagulant with a pH of 3.1 at a level of'7± 0.5% of the weight of skimmed milk satisfies the requirements for protein-herbal clots according to quality indices.
Keywords: щавель; sorrel (Rumex); термокислотна коагуляція; thermo & heat coagulation of proteins; біологічна цінність; biological value; морозиво; ice cream; кафедра технології молока і молочних продуктів